Working Memory Role on Gender towards Language Transfer: Study of Neurolinguistics - Marwati, Sofia; Sastra, Gusdi (OKARA: Jurnal Bahasa dan Sastra, 2019)
Second language acquisition requires many aspects including how the working memory supports the system of the human input system. Working memory has a crucial identity in storing information for a short time. It is a limited complex ability required for holding and manipulating information in a brief period for learning, thinking, giving attention, counting, memorizing, comprehending, and problem-solving. The aims of this research are to predict the role of working memory capacity on males and females and to identify the language transfer in between. The subject of this research consisted of 14 Indonesian students (7 male 7 female) at International Islamic University Malaysia (IIUM). They are signed as postgraduate students of many different majors. Data were taken by using the reading span test of Ronnberg version. Data were analyzed by referring to Baddeley, Hitch, and Ellis. The finding of the research declares that difference gender has different working memory capacity pattern and language transfer. Gender is also a crucial factor in improving second language acquisition.